Colorectal cancer in the young, many questions, few answers - Deen, Kemal I (World J Gastrointest Oncol, 2016)
At a time where the incidence of colorectal cancer, a disease predominantly of developed nations, is showing a decline in those 50 years of age and older, data from the West is showing a rising incidence of this cancer in young individuals. Central to this has been the 75% increase in rectal cancer incidence in the last four decades. Furthermore, predictive data based on mathematical modelling indicates a 124 percent rise in the incidence of rectal cancer by the year 2030 - a statistic that calls for collective global thought and action. While predominance of colorectal cancer (CRC) is likely to be in that part of the large bowel distal to the splenic flexure, which makes flexible sigmoidoscopic examination an ideal screening tool, the cost and benefit of mass screening in young people remain unknown. In countries where the incidence of young CRC is as high as 35% to 50%, the available data do not seem to indicate that the disease in young people is one of high red meat consuming nations only. Improvement in our understanding of genetic pathways in the aetiology of CRC, chiefly of the MSI, CIN and CIMP pathway, supports the notion that up to 30% of CRC is genetic, and may reflect a familial trait or environmentally induced changes. However, a number of other germline and somatic mutations, some of which remain unidentified, may play a role in the genesis of this cancer and stand in the way of a clear understanding of CRC in the young. Clinically, a proportion of young persons with CRC die early after curative surgery, presumably from aggressive tumour biology, compared with the majority in whom survival after operation will remain unchanged for five years or greater. The challenge in the future will be to determine, by genetic fingerprinting or otherwise, those at risk of developing CRC and the determinants of survival in those who develop CRC. Ultimately, prevention and early detection, just like for those over 50 years with CRC, will determine the outcome of CRC in young persons. At present, aside from those with an established familial tendency, there is no consensus on screening young persons who may be at risk. However, increasing awareness of this cancer in the young and the established benefit of prevention in older persons, must be a message that should be communicated with medical students, primary health care personnel and first contact doctors. The latter constitutes a formidable challenge.